System of Environmental Protection from Bacterial Aerosols in Propagators for Microorganisms Cultivation - V.M. Samygin; T.A. Grishkina; L.K. Zhoga; A.Yu. Alexandrov; S.V. Redkozubov; Nguen Tkhi Ngok Min (Проблемы особо опасных инфекций, 2009)
Presented is propagator equipped with environmental protection system against fermentation releases. The unit supplied with vacuum pump, airproof pipeline valves and a series of sequentially connected tanks with disinfectant solutions is placed in a safety box. Shown are the experimental data on comparative evaluation of inactivation properties of authorized decontamination materials as for bacterial aerosols at submerged cultivation of germs.